Migration and degradation in composting environment of active polylactic acid bilayer nanocomposites films: Combined role of umbelliferone, lignin and cellulose nanostructures - Iglesias Montes, Magdalena Luz (2021)
This study was dedicated to the functional characterization of innovative poly(lactic acid) (PLA)-based bilayer films containing lignocellulosic nanostructures (cellulose nanocrystals, CNC or lignin nanoparticles, LNP) and umbelliferone (UMB) as active ingredient (AI), prepared to be used as active food packaging. Materials proved to have active properties associated with the antioxidant action of UMB and LNP. In fact, the combination of both ingredients in the bilayer formulations produced a positive synergic effect inducing the highest antioxidant capacity. The results of overall migration for the PLA bilayer systems combining CNC or LNP and UMB revealed that none of these samples exceeded the overall migration limit required by the current normative for food packaging materials in both non-polar and polar simulants. Finally, all the hydrophobic monolayer and bilayer films were completely disintegrated in composting conditions in less than 18 days of incubation, providing a good insight on the potential use of these materials for application as active and compostable food packaging.